Impact of the National Endoscopy Database (NED) on colonoscopy withdrawal time: a tertiary centre experience. Issue 1 (2nd July 2021) - Shiha, Mohamed G; Al-Rifaie, Ammar; Thoufeeq, Mo
Abstract : Objective: Colonoscopy withdrawal time (CWT) is a key performance indicator affecting polyp detection rate (PDR) and adenoma detection rate (ADR). However, studies have shown wide variation in CWT and ADR between different endoscopists. The National Endoscopy Database (NED) was implemented to enable quality assurance in all endoscopy units across the UK and also to reduce variation in practice. We aimed to assess whether CWT changed since the introduction of NED and whether CWT affected PDR. Methods: We used NED to retrospectively collect data regarding CWT and PDR of 25 endoscopists who performed (n=4459 colonoscopies) in the four quarters of 2019. We then compared this data to their performance in 2016, before using NED (n=4324 colonoscopies). Results: Mean CWT increased from 7.66 min in 2016 to 9.25 min in 2019 (p=0.0001). Mean PDR in the two periods was 29.9% and 28.3% (p=0.64). 72% of endoscopists (18/25) had CWT>6 min in 2016 versus 100% (25/25) in 2019, the longer CWT in 2019 positively correlated with the PDR (r=0.50, p=0.01). Gastroenterology consultants and trainee endoscopists had longer CWT compared with colorectal surgeons both before and after using NED. Conclusion: NED usage increased withdrawal times in colonoscopy. Longer withdrawal times were associated with higher PDR. A national colonoscopy audit using data from NED is required to evaluate whether wide variations in practice across endoscopy units in the UK still exist and to ensure minimum colonoscopy quality standards are achieved.